Pemberdayaan Masyarakat Lokal (Nelayan) Menuju pada Transformasi Masyarakat - Kawulu, Arie Frits (Jurnal Aplikasi Manajemen, 2009)
Societal transformation that run periodically and continuously determined by accurate and valid empowerment idea on the basis of community oriented, the availability of local resources, and active paticipation from stakeholders. The local empowerment needs to look at the potentials owned by groups or individuals wanted to be empowered and dsimiss any obstacles that inhibits social mobility, not merely giving the fish to eat.In this case, the empowerment concept on local inhabitants offered was top-down as well as bottom-up ones settled with attention to all life dimensions of local communities. Looking at local empowerment (fishermen), their life can be improved if when there was fundamental change of their whole life aspects or well-known as the process of social transformation. Empowerment with no looking at transformation phases in their life will result in no life improvement and therefore still live in poverty and poor.